(untitled) (Experimental biology, 2018)
Scorzonera tau-saghyz - endemic of Kazakhstan, capable of accumulate up to 40% of rubber in dry roots and quality is not inferior to rubber hevea. Currently, research work is underway to restore the number of this species, as well as to develop effective and cost-effective biotechnologies for obtaining commercial rubber from the roots of the tau-saghyz. In long-term laboratory experiment carried out mycorrhization of seedlings. As inoculum used fungi Claroideoglomus etunicatum (Schüssler/Walker), Claroideoglomus claroideum (Schüssler/Walker) and Rhizophagus intraradices (Schüssler/Walker). In the roots of infected plants were revealed structures typical for fungi, forming arbuscular mycorrhizae type: non septate mycelium, vesicles and arbuscules. Mycorrhizal infection in the studied samples of S. tau-saghyz roots was 100 %. Infected plants was noticeably better than non-mycorrhizal. The average height and number of leaves of mycorrhizal plants was 1.5 times higher than that of non-mycorrhizal plants, which is proof of the importance of arbuscular mycorrhizae in the life of stenotopic, rare and extinct S. tau-saghyz. The use of endomycorrhizal fungi can significantly contribute to the development of modern, cost-effective biotechnologies aimed at restoring the abundance in nature and obtaining commercial rubber from the roots of tau-saghyz. These studies are particularly relevant at growing demand in the world for natural rubber and the search for alternative sources of natural rubber, in contrast to Hevea. Key words: Scorzonera tau-saghyz Lipsch. et G.G. Bosse, Glomeromycota, Claroideoglomus etunicatum (Schüssler/Walker), Rhizophagus intraradices (Schüssler/Walker), Claroideoglomus claroideum (Schüssler/Walker).